2019
DOI: 10.1016/j.laa.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial convolutions in max-plus algebra

Abstract: Recently, in a work that grew out of their exploration of interlacing polynomials, Marcus, Spielman and Srivastava [21] and Marcus [20] studied certain combinatorial polynomial convolutions. These convolutions preserve real-rootedness and capture expectations of characteristic polynomials of unitarily invariant random matrices, thus providing a link to free probability. We explore analogues of these types of convolutions in the setting of max-plus algebra. In this setting the max-permanent replaces the determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The characteristic maxpolynomial of A (see e.g. [3,14,15]) is a max polynomial where I denotes the identity matrix. We call its tropical roots (the points of nondifferentiability of A (x) considered as a function on [0, ∞) ) algebraic max eigenvalues (or also tropical eigenvalues) of A.…”
Section: Theorem 1 If a ∈ M N (ℝ + ) Thenmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic maxpolynomial of A (see e.g. [3,14,15]) is a max polynomial where I denotes the identity matrix. We call its tropical roots (the points of nondifferentiability of A (x) considered as a function on [0, ∞) ) algebraic max eigenvalues (or also tropical eigenvalues) of A.…”
Section: Theorem 1 If a ∈ M N (ℝ + ) Thenmentioning
confidence: 99%
“…The set of all algebraic max eigenvalues is denoted by trop (A) . For ∈ trop (A) its multiplicity as a tropical root of A (x) (see e.g [3,14,15]) is called an algebraic multiplicity of . It is known that max (A) ⊂ trop (A) [15,Remark 2.3] and that (A) = max{ ∶ ∈ trop (A)} , but in general, the sets max (A) and trop (A) may differ.…”
Section: Theorem 1 If a ∈ M N (ℝ + ) Thenmentioning
confidence: 99%
“…For more information on tropical algebra we refer to the monograph of Butkovič [17]. Min-plus algebra is isomorphic to max-plus algebra, which is the semifield R ∪ {−∞}, where addition is replaced by maximum and multiplication by addition (see e.g., [17,18] and the references there), and also to max-times algebra R + , where addition is replaced by maximum and multiplication is the same as in standard arithmetic (see e.g., [19] and the references there). Tropical algebra is a part of a broader branch of mathematics, called "idempotent mathematics", which was developed mainly by Maslov and his collaborators (see e.g., [20,21]).…”
Section: Tropical Algebramentioning
confidence: 99%
“…Izhakian et al [29,30] showed that systems of tropical polynomials formed from univariate monomials define subsemigroups with respect to tropical addition (maximum). Rosenmann et al [31] created an exact and simple description of all roots of convolutions in terms of the roots of involved maxpolynomials. Wang and Tao [32] introduced the matrix representation of formal polynomials over max-plus algebra to factorize polynomial functions.…”
Section: Introductionmentioning
confidence: 99%